Preparation of indium tin oxide (ITO) thin films by sol-gel method: the effect of coating speed on structural and optical properties - Nor Sarahtul Nadirah, Hairol Nizan (2016)
The transparent conducting indium tin oxide (ITO) thin films were prepared by sol-gel and spin coating technique at various coating speed (500, 1500 and 3000 rpm). ITO thin films containing 8% Sn by weight were successfully prepared by heat treatment at 500 ̊C in this study. The structural and optical properties significantly depend on the coating speed. From the XRD result obtained, the prepared ITO thin film has cubic structure, and (222) is its preferred plane. As the coating speed increase, films shows a lower degree of polycrystallinity. The grain size in the range nanometer decreased with increasing coating speed. The transmittance value of all ITO thin films are more than 90%. The band gap are calculated from plotting product of adsorption coeeficients in photon energy (